2021
DOI: 10.1039/d0sm01367f
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscopic interactions of colloidal particles can suppress millimetre drop splashing

Abstract: The presence of nanoparticles in a millimetric liquid drop impacting on a solid surface can suppress splashing at higher impact velocities. This mechanism is affected by the nanoparticles concentration and the coating molecules at their surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 65 publications
3
12
0
Order By: Relevance
“…Such cases are categorized into droplet disintegration in the present study. The experimental results are similar to the observations of Thoraval et al, where the silicone oil droplets have We = 1500–2000, much larger than the range of our experiments ( We = 100–550). However, the viscosity of liquid droplets considered here is much larger than that (μ = 19 mPa·s, Oh ≈ 0.095) in Thoraval et al Consequently, the Ohnesorge number should be considered as an indispensable parameter in categorizing impact outcomes.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Such cases are categorized into droplet disintegration in the present study. The experimental results are similar to the observations of Thoraval et al, where the silicone oil droplets have We = 1500–2000, much larger than the range of our experiments ( We = 100–550). However, the viscosity of liquid droplets considered here is much larger than that (μ = 19 mPa·s, Oh ≈ 0.095) in Thoraval et al Consequently, the Ohnesorge number should be considered as an indispensable parameter in categorizing impact outcomes.…”
Section: Resultssupporting
confidence: 92%
“…It is noted that Thoraval et al recently found that the suppression of splashing at We ≈ 500 can be caused by silver nanoparticle dispersion, which probably affects the non-Newtonian flow or particle/liquid two-phase flow behaviors and requires additional controlling parameters for phenomenological characterization. In the present study, we used the pure Newtonian fluids (water–glycerol solutions), and the only varying controlling parameters are We and Oh (other controlling parameters are fixed).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of a non-Newtonian droplet on a solid substrate is a subject of many experiments and simulations such as for 3D printing 34,35 , and pesticides 36 applications. It has been shown that a small amount of non-Newtonian solute can make remarkable changes in fluid a) Electronic mail: chezhizhao@tju.edu.cn properties, effectively controlling the flow behavior [36][37][38] . For example, dilute aqueous solutions of a flexible polymer (e.g., polyethylene oxide) can effectively inhibit the process of retracting and rebounding when a droplet impacts on a hydrophobic surface without changing the viscosity of the solution greatly 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The high elongational viscosity of the solution is considered as the reason for the retraction damping during the droplet impact 36 . Further studies indicated that the rheological and surface properties are important factors for the spreading and retraction during the impact of non-Newtonian droplets [37][38][39][40][41] . The rheological properties are always reflected by various physical models in simulation 39,40 .…”
Section: Introductionmentioning
confidence: 99%